1999
DOI: 10.1111/j.1553-2712.1999.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Don't Emergency Department Patients Have Advance Directives?

Abstract: Abstract. Objectives:In 1997 the authors determined that only 27% of their adult ED patients had advance directives (ADs). The purpose of this followup study was to determine the reasons why their adult ED patients do not have ADs. Methods: This prospective study enrolled patients from a convenience sample of representative shifts in the ED selected over a three-month period. Survey questions included demographic information, whether the patients had a life-threatening medical problem, whether they had an AD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
3
28
2
Order By: Relevance
“…Because other ED-based studies were not restricted to elder or institutionalized patients, the prevalence of ADs in our study is nearly double that reported by previous investigators (22%, 27%, and 23%). [7][8][9] This higher prevalence is still disturbingly low when one considers that the Congressional Patient Self-Determination Act of 1991 clearly requires all hospitals and other institutions receiving Medicare or Medicaid funding to promote the use of ADs.…”
Section: Discussionmentioning
confidence: 99%
“…Because other ED-based studies were not restricted to elder or institutionalized patients, the prevalence of ADs in our study is nearly double that reported by previous investigators (22%, 27%, and 23%). [7][8][9] This higher prevalence is still disturbingly low when one considers that the Congressional Patient Self-Determination Act of 1991 clearly requires all hospitals and other institutions receiving Medicare or Medicaid funding to promote the use of ADs.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,16,17,18 The pressing demand to maximize ED throughput and a general consensus that ED clinicians may feel these conversations are best held in a nonchaotic setting with qualified personnel may also hinder early prognostication/goals-of-care discussions. 2,4,18 Admittedly, it is a challenge to predict which ED crisis presentation is a patient's terminal event.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The rapid decision making required for the acute terminal crisis event leaves limited time for dialogue and adds to the challenge of having conversations with family with whom there is no prior established rapport. 8,18 This time may be optimal for PC clinician support to the ED and hence a major role of the PC in early, real-time, determinative decision making, but prompt availability will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Factors found to be predictive of having an AD were older age, having a specialist, having a lifethreatening medical problem, and not being Catholic. 6 In another ED study of 238 patients in Tennessee, Ishihara and colleagues found that 22% of patients had ADs. 5 Of these, 23% brought their ADs along for the ED visit.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Moreover, other studies suggest that even when patients have ADs, the existence or specifics of these directives may not be communicated to primary health care providers. [5][6][7] The emergency department (ED) represents a unique setting where physicians frequently encounter patients for the first time and are unfamiliar with their values and beliefs regarding end-of-life care. Moreover, EDs frequently treat critically ill patients, many of whom are not able to communicate with hospital staff, at times without the benefit of an identified substitute decision maker.…”
Section: Ré Sumémentioning
confidence: 99%